Exchanging experiences of technology partnership : papers... - UNCTAD (UN New YorkUS, 1996)
Provides a conceptual framework for the exchange of experiences at Helsinki. Presents an analysis of challenges and opportunities perceived with regard to technology partnership at the national level, as well as at the level of particular economic sectors. Reviews the importance of networking among economic actors involved in technology partnerships. Presents the recommendations of the expert meeting.